In Trump Administration, a Sharp Divide Over Election Interference. - SANGER, DAVID E. (New York Times, 2018)
The article reports that the alleged hacking and Russian intervention to the 2016 U.S. elections raised mixed opinions from officials to the U.S. President Donald Trump administration including national security adviser H. R. McMaster, Defense Secretary Jim Mattis, and Vice President Mike Pence.